2021
DOI: 10.28932/jmm.v20i2.3133
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan persepsi bimbingan akademik mahasiswa pada sebuah perguruan tinggi swasta di Indonesia

Abstract: This research is about academic advising in bachelor degree of management department in a private university in Bandung City. There are two style of academic advising, prescriptive and developmental academic advising. The result showed developmental academic advising is covered in that department. In this research, the differences in perceptions of academic advising were tested based on gender, origin area of residence, age, year of study, intensity, and frequency of academic advising. The main objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…(4) The academic consulting needs of students are also changing. Before carrying out consultation and suggestion activities, consultants should fully conduct needs analysis on the individual conditions of different students [ 83 ]. (5) Coordination between advisors should be strengthened to avoid situations where advisors give different advice to students for the same event due to their different backgrounds and expectations [ 84 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(4) The academic consulting needs of students are also changing. Before carrying out consultation and suggestion activities, consultants should fully conduct needs analysis on the individual conditions of different students [ 83 ]. (5) Coordination between advisors should be strengthened to avoid situations where advisors give different advice to students for the same event due to their different backgrounds and expectations [ 84 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Academic advising is not just an administrative activity but a meaningful educational one for great achievement in a university (Junita et al, 2020). Therefore, the faculty and study programs need to intensively participate in designing the system that will develop the students intellectually (Sherlywati et al, 2021). The research of Donaldson et al (2016) has shown that guardian lecturers help to shape students' culture using information and features to formulate academic plans, demonstrate decision-making, familiarize undergraduates with campus policies and procedures, as well as allow them to achieve their future careers.…”
Section: Introductionmentioning
confidence: 99%
“…Students believe that the guardian lecturer not only focuses on academic performance but also on holistic development. The second stage shows that there are differences based on gender, regional origin, age, class, advising time intensity, and frequency (Sherlywati et al, 2021). This helps the university design the academic advising process for mature students with a high enough class.…”
Section: Introductionmentioning
confidence: 99%